California agriculture : dimensions and issues - Martin, Philip L., 1949-; Goodhue, Rachael E. (Rachael Evadne); Wright, Brian, 1948 January 1- (Giannini Foundation information series, 2020)
This introduction to California agriculture is funded by the Giannini Foundation of Agricultural Economics and is written by agricultural economists at UC Davis, UC Berkeley, and UC Riverside. Each chapter includes basic data, trends over time, and current issues. Topics examined include land, labor, and water inputs needed to produce the state's farm commodities, the status of major crops and livestock, and the challenges facing the state's agriculture, from climate change and trade to research. The project was supported by the Giannini Foundation of Agricultural Economics, which was established with a 1928 grant to analyze and propose policies to improve California agriculture.